(untitled) (Global Journal of Science Frontier Research, 2015)
This paper describes experiments on the induction of sex reversal in chickens by estrogen inhibitors (letrozole, tamoxifen), demethylating agent 5-azacytidine and retinoic acid (RA). Particular attention is paid to control entry into meiosis of germ cells. The obtained data indicates a partial overlap control of somatic and gametic sex.